用列项法
an=2/(n(n+2))=1/n-1/(n+2)
然后楼主自己写出前几项就会发现前后两项相互约去
最后的结果是3/2-(2n+3)/(n+1).(n+2)
an=[(n+2)-n]/n(n+2)
=(n+2)/n(n+2)-n/n(n+2)
=1/n-1/(n+2)
所以Sn=1-1/3+1/2-1/4+1/3-1/5+1/4-1/6+……+1/(n-1)-1/(n+1)+1/n-1/(n+2)
=1+1/2-1/(n+1)-1/(n+2)
=(3n²+7n+3)/(2n²+6n+4)
an=2/(n(n+2))=1/n-1/(n+2)
∴Sn=1/1-1/3+1/2-1/4+1/3-1/5+……+1/n-1/(n+2)
=3/2-1/(n+1)-1/(n+2)=(3n²+9n)/2(n+1)(n+2)
化简成an=1/n-1/(n+2),求和从a1加到an就是1+1/2-1/(n+1)-1/(n+2)
(n+1)-1/an=[(n+2)-n]/n(n+2)
=(n+2)/n(n+2)-n/2-1/(n+2)
=(3n²+7n+3)/n(n+2)
=1/n-1/(n+2)
所以Sn=1-1/3+1/2-1/4+1/3-1/5+1/4-1/6+……+1/(n-1)-1/(n+1)+1/(n+2)
=1+1/n-1/
1/2